A cross sectional study of hearing thresholds in medical students - Katiyar, V. M. Hemlata; Elango, D.; Prasanna, Vincent (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The hearing thresholds of young adults with no known hearing loss or noise exposure is expected to be closer to 0 dB HL, though with the increasing usage of recreational noise through personal amplification devices there is shift in thresholds noted. Some studies have highlighted the effect of these devices on the hearing thresholds and a general shift of thresholds towards 25 dB. Objective was to determine the audiometric thresholds of a screened sample of medical students with presumed normal hearing. Methods: A total of 103 medical students in the age group of 20 to 23 years were screened and subjected to PTA. The Pure tone average was calculated for air conduction (AC) and bone conduction (BC) separately and also for high frequencies (HF). The average for the female students was compared with that of male students. The right ear average was compared with that of left ear. Results: There was a statistically significant difference with higher thresholds for males in BC and HF, however the difference in AC was not significant. Between the right and left ears, there was statistically significant elevation observed in BC average in the right ear, but no significant difference was found in the HF and AC thresholds. Conclusions: There is evidence of thresholds especially BC, shifting more towards 25 dB HL in young adults considered to have normal hearing. Early screening will help in identifying this and prevent further elevation by judicious use of mobile phones, personal music players and personal listening devices.